2015
DOI: 10.1123/rsj.2014-0036
|View full text |Cite
|
Sign up to set email alerts
|

Learning Goals and the Challenge Course Experience: An Exploratory Study

Abstract: This study explored the short- and long-term ability of a university affiliated challenge course program to provide a lasting, quality experience for college participants aligning with the university's Learning Goals for Graduates (LGGs). The Challenge Course Experience Questionnaire (CCEQ), a newly created assessment tool, was administered to 375 participants in 16 different groups. Participants completed a four to six hour program, consisting of low- and high-course elements. Participants were assessed befor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

3
6
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 17 publications
3
6
0
Order By: Relevance
“…In addition, Statement 1 creatively asks the participant's feeling toward the CC program by giving three categorical options: Prisoner (i.e., "I do not want to be here"), Vacationer (i.e., "I am here to have fun"), or Learner (i.e., "I am here to discover new things about myself and/or others"). The CCEQ is a brief but descriptive measure of CC participants with acceptable levels of internal reliability (α = .60-.85; Schary, Lewis, & Cardinal, 2015). Similarly, the current study showed acceptable levels of internal reliability (CCEQ-pre: α = .71, CCEQpost: α = .76, CCEQ-final: α = .77).…”
Section: Methodssupporting
confidence: 65%
See 4 more Smart Citations
“…In addition, Statement 1 creatively asks the participant's feeling toward the CC program by giving three categorical options: Prisoner (i.e., "I do not want to be here"), Vacationer (i.e., "I am here to have fun"), or Learner (i.e., "I am here to discover new things about myself and/or others"). The CCEQ is a brief but descriptive measure of CC participants with acceptable levels of internal reliability (α = .60-.85; Schary, Lewis, & Cardinal, 2015). Similarly, the current study showed acceptable levels of internal reliability (CCEQ-pre: α = .71, CCEQpost: α = .76, CCEQ-final: α = .77).…”
Section: Methodssupporting
confidence: 65%
“…The Challenge Course Experience Questionnaire (CCEQ; Schary et al, 2015) was delivered at three points: immediately before the CC program, immediately after the CC program, and at the end of the semester (approximately three months after participation). As shown in Table 2, the CCEQ has 10 items (10 items for the CCEQ-pre and the CCEQ-post, eight items for the CCEQ-final) measuring a variety of variables like attitude (i.e., Statement 2) problem solving abilities (i.e., Statement 5), social interaction (i.e., Statement 7), and transferability of skills (i.e., Statement 9).…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations